Looking back and taking stock life stories of discharged youth offenders. - Docena, Pierce S. (2011.)
The paricipants' narratives revealed that prior to the RRCY experience, most of them lived with dysfunctional families in cahotic communities had very low educational attainment, and were in close contact with friends who were already actively engaged in delinquent activities. These predisposing factors surrounding the youth built and fed upon each other's deficiencies to push them into a life of delinquency, the rewarding consequences of which enshared them in a cycle of antisocial behaviors until they were incarcerated and committed to RRCY., In terms of meaning making majority of the participants came up with strikingly attributions for their offense and subsequent incarceration, which is believed to reflect an adaptive mechanism that protects them from the potentially devastating effects of their difficult past experiences. Moreover, all participants had positive evaluations of their stay in the RRCY, which is considered as a time-out experience that provided them an opportunity to reflect on their previous lives and the prospect of change. Upon their discharge, many of them immediately took working in order to augment their family income while others got married and children. Results likewise suggest that distance from crime is a long and difficult process influenced by various factors such as family support, condition of community, intervention of significant persons, having a job, and getting married and having children. Nearly all of the discharged youth offenders are presently struggling with financial difficulties, which they proactively deal with in various ways. Resilience is also assumed to be an important mechanism that helps the participants cope with their struggles and manage their live relatively well. Identify is not as compelling an issue for the present sample contrary to expectations of individuals in their emerging adulthood. Instead, socioeconomic concerns serve as stronger motivators that identify concerns for the discharged youth offenders, suggesting that the concepts of identity (McAdams, 1996) and psychosocial issues (Erikson, 1963) might not be applicable to the present sample due to cultural differences. The participants had very optimistic visions of their future, an adaptive mechanism that makes it easier to face a future that, given their current status, might actually be highly uncertain. Finally, many of the participants evaluated their life stories as having been transformed from "bad" to "good" - another self-enhancing strategy that's gives the discharged youth offenders a sense of agency at having survived difficult experiences as well as a source of hope for a possible good ending to their life stories.
Thesis (Graduate, Master of Arts in Psychology) College of Social Sciences and Philosophy, University of the Philippines, Diliman, Quezon City.
Keywords: Youth -- Offenders; Regional Rehabilitation Center for Youth (RRCY)